Experimental Results of Diver Detection in Harbor Environments Using Single Acoustic Vector Sensor - MAHMOUD, Saier; SALEH, Louay; CHOUAIB, Ibrahim (Archives of Acoustics, 2025)
This paper addresses the detection of divers with an open-circuit scuba. An acoustic vector sensor (AVS), which contains four channels, one for the pressure component, and three for orthogonal particle velocity components is proposed to be used. A novel covariance matrix analysis (CMA) method is presented for estimating the signal power using AVS in three-dimensional measurements. This method is based on solving a quartic equation that relates the determinant and trace of the AVS covariance matrix to the reciprocal of the signalto-noise ratio (SNR) in a three-dimensional isotropic acoustic field with spherical isotropic noise. This method is compared with two traditional methods: the AVS pressure channel power, and the minimum variance distortionless response (MVDR) beamformer, in estimating the acoustic power associated with the diver’s breathing. Experimental data from sea trials demonstrate the capability of all three methods to reconstruct the waveform of the acoustic diver signal and highlight the periodic breathing patterns. The diver’s breathing rate and corresponding power are estimated using the fast Fourier transform (FFT) of the power signal, therefore serving as a key signature for diver detection. The experiment demonstrates that the CMA method gives better diver detection index compared to the other two methods.